PENGARUH MODAL INTELEKTUAL TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Nunki Arun Sudibya, Diva Cicilya; Restuti, MI Mitha Dwi (Universitas Muhammadiyah Surakarta, 2014)
This study examined the effect of intellectual capital on the market value of the companys financial performance as an intervening variable in corporate banking and financial institutions. This study used a -Pulic Value Added Intellectual Coefficients (VAICTM) model to examine the relationship between intellectual capital and the market value of the companys financial performance. The market value is measured by the price to book value (PBV), the companys financial performance is measured by return on equity (ROE). The samples used in this study is the banking companies and financial institutions listed on the Indonesia Stock Exchange (IDX) on 2008-2012. Data obtained 274 samples. This study used linear regression to analyze the data and path analysis to determine the effect of mediation. The results showed that intellectual capital had positive effect on the market value of the company, a positive financial performance, and financial performance may mediate the relationship between intellectual capital with the market value of the company.